Recent advances in the electrolytes for interfacial stability of high-voltage cathodes in lithium-ion batteries. Issue 4 (11th December 2014) - Choi, Nam-Soon; Han, Jung-Gu; Ha, Se-Young; Park, Inbok; Back, Chang-Keun
Abstract : We present the useful processes in the research of functional electrolytes for interfacial stability of high-voltage cathodes in Li-ion batteries. Abstract : Advanced electrolytes with unique functions such as in situ formation of a stable artificial solid electrolyte interphase (SEI) layer on the anode and the cathode, and the improvement in oxidation stability of the electrolyte have recently gained recognition as a promising means for highly reliable lithium-ion batteries with high energy density. In this review, we describe several challenges for the cathode (spinel lithium manganese oxide (LMO), lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (NCM), spinel lithium manganese nickel oxide (LNMO), and lithium-rich layered oxide (Li-rich cathode))-electrolyte interfaces and highlight the recent progress in the use of oxidative additives and high-voltage solvents in high-performance cells.